2016
DOI: 10.1101/gad.290619.116
|View full text |Cite
|
Sign up to set email alerts
|

MEF2 transcription factors are key regulators of sprouting angiogenesis

Abstract: Angiogenesis, the fundamental process by which new blood vessels form from existing ones, depends on precise spatial and temporal gene expression within specific compartments of the endothelium. However, the molecular links between proangiogenic signals and downstream gene expression remain unclear. During sprouting angiogenesis, the specification of endothelial cells into the tip cells that lead new blood vessel sprouts is coordinated by vascular endothelial growth factor A (VEGFA) and Delta-like ligand 4 (Dl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
85
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(93 citation statements)
references
References 68 publications
4
85
0
2
Order By: Relevance
“…This is in line with a recent study by the De Val group56, showing that ETS motifs within the Dll4 intron 3 enhancer are not required for its expression at the angiogenic front. The authors suggest a model in which MEF2 transcription factors cooperate with ETS factors, where ETS provide essential endothelial expression information and MEF2 contribute angiogenic sprout specificity56. Ang1 can also promote Dll4 expression, and here we show that this requires ERG.…”
Section: Discussionsupporting
confidence: 92%
“…This is in line with a recent study by the De Val group56, showing that ETS motifs within the Dll4 intron 3 enhancer are not required for its expression at the angiogenic front. The authors suggest a model in which MEF2 transcription factors cooperate with ETS factors, where ETS provide essential endothelial expression information and MEF2 contribute angiogenic sprout specificity56. Ang1 can also promote Dll4 expression, and here we show that this requires ERG.…”
Section: Discussionsupporting
confidence: 92%
“…The kinetics of this repressive TEL/CTBP complex disassembly are comparable to the assembly of the activating ERG/p300 complex that we report here, suggesting that TEL and ERG dynamically control co-activator/co-repressor recruitment. Recently, VEGF has also been shown to stimulate dynamic exchange of co-repressors for co-activators bound to MEF2 transcription factors (Sacilotto et al, 2016), suggesting that several families of transcription factors may coordinate VEGFdependent sprouting angiogenesis. Indeed, ETS proteins interact with multiple transcription factor families (Carrere et al, 1998;De Val et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…They further revealed a protective role for Mef2c in inflammation in that LPS-induced leukocyte adhesion in retinal vessels is increased in Mef2c deleted endothelium 15 . While deletion of Mef2c alone did not affect angiogenesis, combined endothelial-specific deletion of Mef2a and -c revealed that they regulate angiogenic sprouting and are direct transcriptional regulators of Dll4 in angiogenic tip cells 29 .…”
Section: Introductionmentioning
confidence: 90%
“…In vivo experiments supporting a role for Mef2 in the endothelium have been restricted to the retinal vasculature and developing embryo 15,28,29 . These experiments show that Mef2c is important for protection to hyperoxia and pathological angiogenesis, partly through Hmox1 regulation 28 .…”
Section: Introductionmentioning
confidence: 99%